Ethnic Reindeer Herders:Groupness among reindeer-herding Sámi in Northwest Finnish Lapland - Nykänen, Tapio; Valkeapää, Leena (Ethnicities, 2018)
In the article, we examine the ethnic groupness among Sámi reindeer herders in Northwest Finnish Lapland. According to our results, reindeer herders recognize different groupnessess. Sáminess is perceived as an ethnic and often local, family-related groupness. Moreover, Sámi ethnicity is closely bound to the local herding life on the fells, in the cultural landscape of nomadism. Finnishness, on the other hand, involves meanings relating to the state and nation in particular. The interviews provide indications of the general rise of Sámi culture, the long-term influence of Finnish culture and the state and the multidimensional nature of ethnicities in everyday life, that is, an overlapping and richness of ethnicities and identifications.